Pendampingan Budidaya Maggot untuk Penangangan Sampah Organik di Desa Tampo Kecamatan Cluring Kabupaten Banyuwangi - Syafaatullah, Lalu Muhammad; Wayan Prabudi Sathya Hindu Sambawa; I Gede Gandi Arya Utama; Nelly Rosanty Safny; Maiser Syaputra (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
The Tampo Village community, Cluring District, Banyuwangi, East Java is located in an area with residential areas, rice fields and fruit plantations. Organic waste is one of the most important problems if not prevented and also the lack of public knowledge regarding how to process organic waste makes it a problem in itself. Maggots or black soldier fly larvae (Hermetia illicens) are rotting organisms because they have the habit of eating organic materials and maggots have high protein. In this community service activity, the KKN-MBKM group of Mataram University invited the Tampo Village community to participate in the socialization, training and mentoring of organic waste processing based on maggot cultivation which aims to provide understanding and skills about maggot cultivation. Thus, the Tampo Village community can have new business opportunities, namely maggot cultivation and contribute to environmental sustainability.